Cathodic electrodeposition of Cu2s thin film for solar energy conversion - Anuar, K; Zainal, Z; Hussein, M.Z; Saravanan, N; I, Haslina (Elsevier, 2002)
Cathodic electrodeposition in the presence of EDTA in aqueous solution was used to prepare Cu2S thin film deposited on Ti substrate. The effect of deposition potential, concentration and deposition time was studied to determine the optimum condition for electro-deposition process. Cyclic voltammetry was performed to elucidate the electrodic processes that occur while potentials for electrodeposition were applied to determine the optimum potential for electrodeposition. The thin films are characterised by X-ray diffractometry. The photoactivity of the deposited films and their conduction types were evaluated using photoelectrochemical technique. The band gap energy and type of optical transitions were determined from optical absorbance data.